Biomechanical risk factors for ACL injury differ between the sexes when performing a high-intensive exergame - Michelle C. Haas; Anna L. Martin-Niedecken; Larissa Wild; Leander Schneeberger; Eveline S. Graf (Current Issues in Sport Science (CISS), 2024)
Introduction Incidence rates in anterior cruciate ligament (ACL) injuries, which are linked to multiple factors, are higher in females than males (Sutton & Bullock, 2013). However, the main contributors to the difference in risk are biomechanical factors such as increased knee valgus (KV), knee internal rotation (KIR), or decreased hip flexion (HF; Seyedahmadi et al., 2022). Returning back to sports after an injury requires extensive rehabilitation as well as training of dual-task situations in order to be physically and cognitively prepared. Exergaming represents a dual task including a cognitive and a motor component and may be used as training modality during rehabilitation. It is known that performing a dual-task leads to altered landing movement patterns in healthy athletes (Dai et al., 2018). Before an exergame for rehabilitation after ACL injury can be implemented and tailored to the specific needs of female and male athletes, the movement patterns of males and females need to be understood. Therefore, the aim of this study was to identify biomechanical differences between males and females when performing a high-intensive exergame. Methods Using 3D-motion capture (Vicon) kinematics were measured in 18 healthy athletes (9 male, 9 female) during a 25-min exergame (Sphery Racer, ExerCube). The exergame included nine different exercises of which 8 were used for analysis. The exercises were separated into neutral (squat, jump, burpee) and side-specific exercises (low-touch, mid-touch, high-touch, punch, lunge). For analysis, the maximal KV, maximal KIR, and the minimal HF were extracted during 10-30° knee flexion. These maximal values were then compared between the sexes, the exercises, and both legs with a linear mixed model, for each the neutral and the side-specific exercises. Results A main effect of sex was only found for side-specific exercises in KIR (F(1, 16) = 6.1, p = .02) with females exhibiting higher values. For KV and HF in side-specific exercises as well as all variables in neutral exercises, no significant main effect for sex was found. However, there was a main effect of exercise in KV; KIR, and HF in neutral (p < .001) as well as in side-specific exercises (p < .001). Discussion/Conclusion Differences in KIR between males and females primarily exist during touches and punches. Therefore, exergames should incorporate this fact to counteract increased risk for knee injuries in females. References Dai, B., Cook, R. F., Meyer, E. A., Sciascia, Y., Hinshaw, T. J., Wang, C., & Zhu, Q. (2018). The effect of a secondary cognitive task on landing mechanics and jump performance. Sports Biomechanics, 17(2), 192–205. https://doi.org/10.1080/14763141.2016.1265579 Seyedahmadi, M., Minoonejad, H., Karimizadeh Ardakani, M., Heidari, Z., Bayattork, M., & Akbari, H. (2022). What are gender differences in lower limb muscle activity during jump-landing tasks? A systematic review and meta-analysis. BMC Sports Science, Medicine & Rehabilitation, 14(1), Article 77. https://doi.org/10.1186/s13102-022-00469-3 Sutton, K. M., & Bullock, J. M. (2013). Anterior cruciate ligament rupture: Differences between males and females. The Journal of the American Academy of Orthopaedic Surgeons, 21(1), 41–50. https://doi.org/10.5435/jaaos-21-01-41